POPULATION MOBILITY AND TRADE CONTACTS IN THE GOLDEN TRIANGLE: THAILAND, MYANMAR AND LAOS - I Ketut Ardhana (Jurnal Kependudukan Indonesia, 2007)
The border issue has become a significant problem in Southeast Asia since the end of the Second World War. Focused in the border regions in Thailand, Myanmar and Laos, this paper looks at the factors which have come to the fore, such as, those around economic gaps, cultural and social relations and movement of people who are not listed or are undocumented immigrants in the cross borders. The developments in the borders contribute to the improvements to the area which we can see in the development of trade contacts for instance, through the Mekong River to Luang Prabang and onto the remote areas in the eastern part of Laos. Such conditions are due to the development of a trans-national economy, new economic growth and trade activities. This study gives a better understanding of the trade contacts in the border regions in Southeast Asia, especially a better understanding of such issues that may be shared by Indonesia.Keywords: Population mobility, trade contacts, the Golden Triangle and regional cooperation